2019
DOI: 10.1039/c9tb00181f
|View full text |Cite
|
Sign up to set email alerts
|

Albumin enhances PTX delivery ability of dextran NPs and therapeutic efficacy of PTX for colorectal cancer

Abstract: The nanoassemblies of Dex6k–BSA–PTX and the pH-responsive drug release for anti-tumor applications in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…BCNDs play a protective role on the heart, kidney, and other tissues. This conclusion is similar to that of other nanotube drug delivery systems (Dong et al, 2017;Zhang et al, 2019c). In addition to its therapeutic effect on tumors, drug-loaded nanodrops also show a protective trend for other organs.…”
Section: Groupsupporting
confidence: 87%
See 1 more Smart Citation
“…BCNDs play a protective role on the heart, kidney, and other tissues. This conclusion is similar to that of other nanotube drug delivery systems (Dong et al, 2017;Zhang et al, 2019c). In addition to its therapeutic effect on tumors, drug-loaded nanodrops also show a protective trend for other organs.…”
Section: Groupsupporting
confidence: 87%
“…The mechanism of nanocarrier-targeted therapy is to enter the lesion area from the circulation through passive or active targeting. Passive targeting is mainly achieved through enhanced permeability and retention (EPR) effects (Zhang et al, 2019c). Then, nanocarriers can enter the target cells by endocytosis or other patterns, such as ultrasound-targeted microbubble destruction (UTMD) ( Figure 10).…”
Section: Groupmentioning
confidence: 99%
“…5 From these viewpoints, the development of watersolubilizing techniques is urgently required for hydrophobic compounds to accelerate drug discovery by expanding and opening the bioavailability of lead compounds. 8 To improve the water solubility of hydrophobic compounds, several approaches have been employed such as conjugation with hydrophilic moieties, 9 pH adjustment, 10,11 cosolvency, 10,12 the use of surfactant, 13,14 and encapsulation. 9,15-17 Among these approaches, complexation with biocompatible molecules such as phospholipids 18 and polysaccharides 9,16,17 is a robust strategy because this approach does not require conjugation techniques, which can cause unfavorable side effects in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Core-shell polymeric NPs are biphasic nanomaterials made up of core (blue) and shell (brownish-orange) structures, as shown in Figure 1A(i). These NPs can be prepared from various biocompatible polymers such as silk fibroin, dextran, hyaluronic acid, polyethylene glycol, zwitterionic polymer, and polypeptides [17][18][19][20][21][22]. Previous studies reported that the core-shell structures could combine multiple functionalities within the layers, thereby forming the 'smart' nanocomposite fabrication strategy.…”
Section: Core-shell Nanoparticlesmentioning
confidence: 99%